A correlative optical microscopy and scanning electron microscopy approach to locating nanoparticles in brain tumors. (January 2015) - Kempen, Paul J.; Kircher, Moritz F.; de la Zerda, Adam; Zavaleta, Cristina L.; Jokerst, Jesse V.; Mellinghoff, Ingo K.; Gambhir, Sanjiv S.; Sinclair, Robert
Highlights: Correlative OM/SEM enables accurate localization of nanoparticles in tissue. Gold core nanoparticles appear as bright regions in backscattered electron imaging in the SEM. Nanoparticles were located only within areas of mouse brain containing tumor cells. Abstract: The growing use of nanoparticles in biomedical applications, including cancer diagnosis and treatment, demands the capability to exactly locate them within complex biological systems. In this work a correlative optical and scanning electron microscopy technique was developed to locate and observe multi-modal gold core nanoparticle accumulation in brain tumor models. Entire brain sections from mice containing orthotopic brain tumors injected intravenously with nanoparticles were imaged using both optical microscopy to identify the brain tumor, and scanning electron microscopy to identify the individual nanoparticles. Gold-based nanoparticles were readily identified in the scanning electron microscope using backscattered electron imaging as bright spots against a darker background. This information was then correlated to determine the exact location of the nanoparticles within the brain tissue. The nanoparticles were located only in areas that contained tumor cells, and not in the surrounding healthy brain tissue. This correlative technique provides a powerful method to relate the macro- and micro-scale features visible in light microscopy with the nanoscale features resolvable in scanning electron microscopy.